Low-coverage, whole-genome sequencing of Artocarpus camansi (Moraceae) for phylogenetic marker development and gene discovery(1) - Gardner, Elliot M. (Appl Plant Sci, 2016)
PREMISE OF THE STUDY: We used moderately low-coverage (17×) whole-genome sequencing of Artocarpus camansi (Moraceae) to develop genomic resources for Artocarpus and Moraceae. METHODS AND RESULTS: A de novo assembly of Illumina short reads (251,378,536 pairs, 2 × 100 bp) accounted for 93% of the predicted genome size. Predicted coding regions were used in a three-way orthology search with published genomes of Morus notabilis and Cannabis sativa. Phylogenetic markers for Moraceae were developed from 333 inferred single-copy exons. Ninety-eight putative MADS-box genes were identified. Analysis of all predicted coding regions resulted in preliminary annotation of 49,089 genes. An analysis of synonymous substitutions for pairs of orthologs (Ks analysis) in M. notabilis and A. camansi strongly suggested a lineage-specific whole-genome duplication in Artocarpus. CONCLUSIONS: This study substantially increases the genomic resources available for Artocarpus and Moraceae and demonstrates the value of low-coverage de novo assemblies for nonmodel organisms with moderately large genomes.